2022
DOI: 10.3389/fgene.2022.821650
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of FBLN5 to Unstable Plaques in Carotid Atherosclerosis via mir128 and mir532–3p Based on Bioinformatics Prediction and Validation

Abstract: FBLN5, a member of the short fibulins in the fibulin family of extracellular matrix/matricellular proteins, is involved in interactions with components of the basement membrane and extracellular matrix proteins. It plays key roles in endothelial tissues in many vascular diseases. In this study, the relationship between FBLN5 and carotid atherosclerotic plaque stability as well as the regulatory roles of miRNAs were evaluated. Differential gene expression analyses and weighted gene co-expression network analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…FBLN5 is a member of the fibronectin family and is essential for elastic fiber formation. It was discovered that FBLN5 may play an important role in carotid atherosclerosis via has-mir-128 and has-mir-532-3p ( Zheng et al, 2022 ). PPP1R12A, also known as MYPT1, is a key regulator of protein phosphatase 1C.…”
Section: Discussionmentioning
confidence: 99%
“…FBLN5 is a member of the fibronectin family and is essential for elastic fiber formation. It was discovered that FBLN5 may play an important role in carotid atherosclerosis via has-mir-128 and has-mir-532-3p ( Zheng et al, 2022 ). PPP1R12A, also known as MYPT1, is a key regulator of protein phosphatase 1C.…”
Section: Discussionmentioning
confidence: 99%
“…51) A bioinformatic study showed an association between miR-128 and plaque instability. 52) A study analyzed the role of miR-128 and miR-146a in macrophage-derived extracellular vesicles in the development of atherosclerosis and suggested that miR-146a might have an important role. 53) MiR-100 can suppress chronic vascular inflammation by stimulating autophagy in endothelial cells, inhibiting atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin enhances cell-to-cell adhesion in the cellular microenvironment and also affects cell behavior [ 18 ]. Fibulin-5 (FBLN5), a fibrin, has been shown to enhance endothelial cell adhesion [ 19 ]. FBLN5 reduced the invasion, mammospheres formation, and proliferation capacity of cancer cells via silencing β-catenin phosphorylation in breast cancer and NSCLC, acting as a cancer suppressor gene [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%